EXAMINE THE ATTITUDE OF TAX PAYERS TOWARD COLLECTION of TURNOVER TAX CATEGORY "B" TAX PAYERS IN ETHIOPIA, SOUTH GONDER ZONE - NEGATU, BAHARU SISAY; WALIA, Dr. NIDHI (The journal of contemporary issues in business and government, 2023)
The way the government raises revenue is through taxation. The payment of money through taxes from residents is a requirement of every government in the globe. The government could not function without tax revenue to support its operations. A nation's tax income has consistently been characterized by high tax rates. The problem of tax collection and assessment stands from fairness or equity/ justice, the purpose of the study is to examining the attitude of tax payers toward collection of turnover tax category "B" tax payers in Ethiopia, Amhara region, south Gonder zone. The study has defined geographical, conceptual, and time-span boundaries, and the researcher chooses an exploratory research design with a mixed research approach. The study's findings will be helpful to the government, stakeholders, and others. The researcher used the probability sampling design technique, simple random/chance sampling, to select representatives from taxpayers because this technique is most appropriate if the population element is highly homogeneous, and the non-probability sampling system, convenience sampling/purposive sampling technique, is taken to select sample from employees. The target population of the study was 797, from which 266 samples were taken using T. Yamane's formula. Both primary and secondary sources of data can be used to gather information, which is then analyzed using descriptive statistics and inferential statistics tools, the finding of the study reveals that attitude of taxpayer and the collection of turnover tax collection have strong positive correlation and government must work on fairness as a first remedial and creation of awareness for both employees and taxpayers.